Complete works of Swami Vivekananda - Vivekananda, Swami (Kolkata Advaita Ashram, 2021)
This is the 1st volume of 9 volumes that comprise the collected works of Swami Vivekananda. Much of the material was given as lectures during his visits to the West. Of special interest are Swami Vivekananda's Addresses at the World Parliament of Religions given in Chicago on September 11th, 1893. Also included are Karma Yoga and Raja Yoga</emi> in addition to a treasure trove of material of various lectures and
Keywords: Religion